Cannabis exposure as an interactive cardiovascular risk factor and accelerant of organismal ageing: a longitudinal study. Issue 11 (7th November 2016) - Reece, Albert Stuart; Norman, Amanda; Hulse, Gary Kenneth
Abstract : Objectives: Many reports exist of the cardiovascular toxicity of smoked cannabis but none of arterial stiffness measures or vascular age (VA). In view of its diverse toxicology, the possibility that cannabis-exposed patients may be ageing more quickly requires investigation. Design: Cross-sectional and longitudinal, observational. Prospective. Setting: Single primary care addiction clinic in Brisbane, Australia. Participants: 11 cannabis-only smokers, 504 tobacco-only smokers, 114 tobacco and cannabis smokers and 534 non-smokers. Exclusions: known cardiovascular disease or therapy or acute exposure to alcohol, amphetamine, heroin or methadone. Intervention: Radial arterial pulse wave tonometry (AtCor, SphygmoCor, Sydney) performed opportunistically and sequentially on patients between 2006 and 2011. Main outcome measure: Algorithmically calculated VA. Secondary outcomes: other central haemodynamic variables. Results: Differences between group chronological ages (CA, 30.47±0.48 to 40.36±2.44, mean±SEM) were controlled with linear regression. Between-group sex differences were controlled by single-sex analysis. Mean cannabis exposure among patients was 37.67±7.16 g-years. In regression models controlling for CA, Body Mass Index (BMI), time and inhalant group, the effect of cannabis use on VA was significant in males (p=0.0156) and females (p=0.0084). The effect size in males was 11.84%. A dose–response relationship was demonstrated with lifetime exposure (p<0.002) additional to that of tobacco and opioids. In both sexes, the effect of cannabis was robust to adjustment and was unrelated to its acute effects. Significant power interactions between cannabis exposure and the square and cube of CA were demonstrated (from p<0.002). Conclusions: Cannabis is an interactive cardiovascular risk factor (additional to tobacco and opioids), shows a prominent dose–response effect and is robust to adjustment. Cannabis use is associated with an acceleration of the cardiovascular age, which is a powerful surrogate for the organismal–biological age. This likely underlies and bi-directionally interacts with its diverse toxicological profile and is of considerable public health and regulatory importance.